Maglev trains : key underlying technologies /: key underlying technologies. ([2015]) - (Of Xi nan jiao tong da xue (China)), Liu, Zhigang; Long, Zhiqiang; (Of Guo fang ke xue ji shu da xue (China)), Li, Xiaolong
No abstract available